Understanding the World Resource Pack KG - THE CITY SCHOOL (Lahore THE CITY SCHOOL)
This resource pack provides kindergarten students with learning materials and activities focused on understanding their surroundings and the world around them.
Designed for Kindergarten (KG) students to explore topics about the world around them.
Designed for kindergarten students.
Keywords: Early childhood education-World knowledge for children